Biofidelic dynamic compression of human cortical spheroids reproduces neurotrauma phenotypes - Aaron R. Shoemaker; Ian E. Jones; Kira D. Jeffris; Gina Gabrielli; Alyssa G. Togliatti; Rajeswari Pichika; Eric Martin; Evangelos Kiskinis; Colin K. Franz; John D. Finan (The Company of Biologists, 2021)
Fundamental questions about patient heterogeneity and human-specific pathophysiology currently obstruct progress towards a therapy for traumatic brain injury (TBI). Human in vitro models have the potential to address these questions. Three-dimensional spheroidal cell culture protocols for human-origin neural cells have several important advantages over their two-dimensional monolayer counterparts. Three-dimensional spheroidal cultures may mature more quickly, develop more biofidelic electrophysiological activity and/or reproduce some aspects of brain architecture. Here, we present the first human in vitro model of non-penetrating TBI employing three-dimensional spheroidal cultures. We used a custom-built device to traumatize these spheroids in a quantifiable, repeatable and biofidelic manner, and correlated the heterogeneous mechanical strain field with the injury phenotype. Trauma reduced cell viability, mitochondrial membrane potential and spontaneous synchronous electrophysiological activity in the spheroids. Electrophysiological deficits emerged at lower injury severities than changes in cell viability. Also, traumatized spheroids secreted lactate dehydrogenase, a marker of cell damage, and neurofilament light chain, a promising clinical biomarker of neurotrauma. These results demonstrate that three-dimensional human in vitro models can reproduce important phenotypes of neurotrauma in vitro.